“La efectivización de la separación de las personas privadas de libertad durante la ejecución de la pena, para lograr su rehabilitación y reinserción social”. - GUERRERO ENCALADA, STEVENT GERMÁN (2021)
The present academic degree dissertation entitled “The effective separation of persons deprived of liberty during the enforcement of the punishment, to achieve rehabilitation and social readaptation”, which emerges from the analysis made of the current situation of Ecuadorian prisons, that reflects a reality of the penitentiary system with a big crisis and as a result, 158 persons deprived of liberty have lost their lives in the states of emergency declared in the last three years. In this manner, based on the investigation developed by Sistema Nacional de Prevención contra la Tortura or the national prevention system against torture, in Ecuadorian prisons, it has evinced that one problem is the wrong application of separation of persons inside prisons, because nowadays occurs that the most dangerous persons live together with less dangerous prisoners, also minors share spaces with adult people who are experienced in crime commitment, this makes the psychological treatment, something impossible, for these reasons, the rehabilitation centers has been cataloged by experts as crime refinement places. As consequence, there has been broken some rights of persons 4 deprived of liberty, as the personal integrity and security and the effective administrative protection. To demonstrate the efficiency of the present degree dissertation there were applied some materials and methods, as also interviews and surveys which were useful to establish a legal reform project to Código Orgánico Integral Penal, with the aim of guarantee that the rights of the persons deprived of liberty would be respected. Therefore, murders, violations and injuries can be prevented inside penitentiaries, separating persons is indispensable but there has to be included age parameters to allow persons deprived of liberty of high, medium and low danger to rehabilitate according to the psychological individual treatment, to achieve their social readaptation.